Removing co-occurring contaminants of arsenic and vanadium with full-scale arsenic adsorptive media systems - Thomas J. Sorg (IWA Publishing, 2021)
The U.S. Environmental Protection Agency conducted an Arsenic Demonstration Program (ADP) whereby 50 full, small-scale arsenic removal treatment systems were evaluated for removing arsenic to below the maximum contaminant level of 10 μg/L and their operating cost for a minimum of 1 year. The majority (28) of the systems installed were adsorptive media (AM) technology with the media replaced when exhausted. This paper reports on the results of two ADP projects and two laboratory rapid small-scale column tests (RSSCTs) using the iron-based media, Bayoxide E33 (E33) AM for the removal of arsenic (As) and the co-occurring contaminants (COCs) of vanadium and to a lesser degree fluoride (F) and nitrate (NO3). The ADP studies found that the AM effectively removed the COC of V, but with a lower removal capacity than of As. One ADP study found the AM to be ineffective for the removal of F and NO3. The RSSCT conducted on two other source waters also found vanadium to be removed by the same AM. The study results suggested the AM selectively sequence of As > V > F = N. The study also investigated the AM to achieve an As limit of 5 μg/L. The AM was found to reduce As to below 5 μg/L with around 30% shorter treatment run lengths. HIGHLIGHTS The iron-based adsorptive media (AM), E33, designed for arsenic removal, are also effective for removing vanadium as a co-occurring contaminant, but with a lower removal capacity than for As.; The iron-based AM, E33, are capable of reducing arsenic to less than 5 μg/L with around 30% shorter treatment run lengths than that achieved with a cut-off limit of 10 μg/L.;